Pemodelan Citra Akuifer Menggunakan Metode Geolistrik - Djereng, Jeris Habfrons Wiatri; Simpen, I Nengah; Suharta, I Wayan Gede (BULETIN FISIKA, 2017)
Has been done research on modeling the image of the aquifer using geoelectric method. This  research was conducted on 7 conditions by taking one data at each condition there is condition without being given a model, model conditions flats have not given water and by water, aquifer conditions concave not given water and by water, and aquifer conditions veined not given water and by water this so can get to see the image  data inversion results  of resistivity using Res2dinv. Modeling the aquifer flat using geoelectric method obtained the image in the form of layers of images with different colors in which this is due to the material composition and water content are different. Modeling the concave aquifer using geoelectric obtained the aquifer at a depth of 15-30 cm with blue color because in this area the water content is more than other areas. Modeling a branched aquifer using geoelectric method obtained the image in the form of two points aquifer detached in blue, this is two water sources. In the image modeling of aquifers using geoelectric method the resistivity value lower aquifer region compared to other regions as indicated by the color of light blue until dark.